ANALISIS PERAMALAN JUMLAH TABUNGAN HAJI BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) AMANAH UMMAH PADA MASA PANDEMI COVID-19 - Suhartini, Shinta; Thantawi, Tubagus Rifqy; Mursyidah, Azizah (SAHID BANKING JOURNAL, 2023)
This research was motivated by the Covid-19 pandemic which resulted in the Kingdom of Saudi Arabia restricting the pilgrims, and also suppressing the growth of Hajj savings in Indonesia. Therefore, the decline in economic growth due to the Covid-19 pandemic has increased the number of hajj cancellations and reduced the number of new hajj registrations. Forecasting is a method for estimating a future value using past data. This research was conducted at the Amanah Ummah BPRS which has a Hajj savings product, the forecasting is carried out using a linear trend mathematical equation model, a quadratic trend and an exponential trend. Choose the smallest method of the 3 methods because the smaller the forecast error value, the more accurate the results and can produce the optimal number. Mean Square Error (MSE) Linear trend of 73099,70379, Mean Square Error (MSE) of Quadratic Trend of 73140,71139 and Mean Square Error (MSE) of Exponential Trend of 74836,49328 From the selected forecasting results is Mean Square Error (MSE) Linear trend. And it was found that the total number of Hajj savings in December 2023 was 346,27222421 rounded up to 374.